Oncogenic role and drug sensitivity of ETV4 in human tumors: a pan-cancer analysis - Zhang, Rui; Peng, Yanfang; Gao, Zhe; Qian, Jing; Yang, Kang; Wang, Xinfa; Lu, Wenjing; Zhu, Yongjie; Qiu, Dezhi; Jin, Tong; Wang, Gang; He, Junping; et al. (Frontiers in Oncology, 2023)
Abstract Background: Increasing evidence supports a relationship between E twenty-six variant transcription factor 4 (ETV4) and several cancers, but no pan-cancer analysis has been reported. Methods: The present study surveyed the effects of ETV4 on cancer using RNA sequencing data obtained from The Cancer Genome Atlas and GTEx, and further explored its role in drug sensitivity using data from Cellminer. Differential expression analyses were conducted for multiple cancers using R software. Cox regression and survival analysis were employed to calculate correlations between ETV4 levels and survival outcomes in multiple cancers using the online tool Sangerbox. ETV4 expression was also compared with immunity, heterogeneity, stemness, mismatch repair genes, and DNA methylation among different cancers. Results: ETV4 was found to be significantly upregulated in 28 tumors. Upregulation of ETV4 was associated with poor overall survival, progression free interval, disease-free-interval, and disease specific survival in several cancer types. Expression of ETV4 was also remarkably correlated with immune cell infiltration, tumor heterogeneity, mismatch repair gene expression, DNA methylation, and tumor stemness. Furthermore, ETV4 expression seemed to affect sensitivity to a number of anticancer drugs. Conclusions: These results suggest that ETV4 may be useful as a prognostic factor and therapeutic target.